Basin motives: Sleuths uncover a brazen case of cyber-mischief. (Economist, 2020)
The article informs about an increase in hacking attacks faced by global business enterprises. It mentions that Honda, has announced that its computers had been locked down by ransomware; and victims were bombarded daily with crafted emails whose details suggested the hackers knew quite a bit about them. It mentions about several targets that were involved in a campaign called "ExxonKnew", that alleges that ExxonMobil, spent deliberately playing down the severity of climate change.